Aplicação de modelos de avaliação por múltiplos no Brasil - Saliba, Rafael Victal (2005)
Based on international literature, we test the performance of a number of Value Drivers commonly used for evaluating companies by finance practioners, through simple regression models of the cross-section type which estimate Market Multiples (ß’s of models). By using data on companies listed with the São Paulo Stock ExchangeBovespa, we are able to diagnose the behavior of several multiples in the period between 1994-2004, with an outlook also on the particularities of the economic activities performed by the sample companies (and their possible impacts on the performance of each Value Driver) through a subsequent analysis with segregation of companies in the sample by sectors. Extrapolating simple multiples evaluation standards used by analysts from the main financial institutions in Brazil, we find that adjusting the ratio formulation to allow for an intercept does not provide satisfactory results in terms of pricing erros reduction. Results found may not be generically representative, given the limited availability of data and the restrictions set upon database acquisition.